ANALISIS MORFOLOGIS BAHASA IKLAN LAYANAN MASYARAKAT BIDANG KESEHATAN - Ubaidillah; Wevi Lutfitasari; Maulid Taembo (Universitas Hamzanwadi, 2026)
This study aims to examine the use of affixation and reduplication in the language of public service health advertisements on the Instagram account of the Bangkalan Regency Health Office. A descriptive qualitative approach was employed. Data collection was carried out through an observation technique, in which the researchers closely examined public service advertisement posts on the official Instagram account of the Bangkalan Regency Health Office, then recorded words, phrases, or sentences containing affixation and reduplication processes onto data cards. The collected data were analyzed through three stages: identification of affixation and reduplication forms, classification based on morphological process types, and description of their linguistic functions in constructing persuasive messages. The findings show that affixation—in the forms of prefixes, suffixes, and confixes—is highly dominant in expressing meanings related to actions, processes, and states associated with disease prevention efforts. Conversely, reduplication is absent from the data, confirming that health advertisement language prioritizes clarity and directness. These findings imply that advertisement designers need to strategically consider morphological choices to make health messages more communicative, easily understood, and effective in influencing public awareness and healthy living behaviors.